Achieving the Recommended Endotracheal Tube Cuff Pressure: A Randomized Control Study Comparing Loss of Resistance Syringe to Pilot Balloon Palpation - Fred Bulamba; Andrew Kintu; Nodreen Ayupo; Charles Kojjo; Lameck Ssemogerere; Agnes Wabule; Arthur Kwizera (Anesthesiology Research and Practice)
Background. Both under- and overinflation of endotracheal tube cuffs can result in significant harm to the patient. The optimal technique for establishing and maintaining safe cuff pressures (20–30 cmH2O) is the cuff pressure manometer, but this is not widely available, especially in resource-limited settings where its use is limited by cost of acquisition and maintenance. Therefore, anesthesia providers commonly rely on subjective methods to estimate safe endotracheal cuff pressure. This study set out to determine the efficacy of the loss of resistance syringe method at estimating endotracheal cuff pressures. Methods. This was a randomized clinical trial. We enrolled adult patients scheduled to undergo general anesthesia for elective surgery at Mulago Hospital, Uganda. Study participants were randomized to have their endotracheal cuff pressures estimated by either loss of resistance syringe or pilot balloon palpation. The pressures measured were recorded. Results. One hundred seventy-eight patients were analyzed. 66.3% (59/89) of patients in the loss of resistance group had cuff pressures in the recommended range compared with 22.5% (20/89) from the pilot balloon palpation method. This was statistically significant. Conclusion. The loss of resistance syringe method was superior to pilot balloon palpation at administering pressures in the recommended range. This method provides a viable option to cuff inflation.